Casting of Fe-(2–12)Mn-(4–14)Al-(0.09–0.7)C low-density steel via artificial slag practice - GÜNDÜZ, OĞUZHAN (My University, 2022)
© 2022In this research theoretical and practical studies have been highlighted about alloy design, casting and steel-slag interaction. The use of a protective slag layer was identified as an advantageous method in the production of low-density steels. For the first time in this study, a unique synthetic steelmaking (CaO/Al2O3:1.57) slag was implemented in an induction furnace with no vacuum chamber to produce high aluminum in steel. This study showed that manganese and aluminum directly influence the solidification structure and carbide formation. Coarser k-carbides have been detected at grain boundaries in austenite as-cast matrix when the Aluminum increases in the low-density steel.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; MALZEME BİLİMİ, KOMPOZİTLER; FİZİK, YOĞUN MADDE; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; PHYSICS; ENGINEERING, MECHANICAL; MATERIALS SCIENCE, COMPOSITES; PHYSICS, CONDENSED MATTER; General Materials Science; Physical Sciences; Condensed Matter Physics; Mechanics of Materials; Mechanical Engineering; Low-density steels; Cast; Artificial slag usage; Induction furnace melting; Solidification; MECHANICAL-PROPERTIES; AL